Cost efficient implementation of multistage symmetric repackable networks - Chakrabarty, Dr. Amitabha; Collier, Dr. Martin (© 2011 IGI Global, 2016)
This article was published in International Journal on Grid and High Performance Computing [© 2011 IGI Global] and the definite version is available at : http://www.igi-global.com/viewtitlesample.aspx?id=60251&ptid=48098 t=cost+efficient+implementation+of+multistage+symmetric+repackable+networks The article website is at: http://www.igi-global.com/journal/international-journal-grid-high-performance/1105